2019
DOI: 10.1186/s11782-019-0057-y
|View full text |Cite
|
Sign up to set email alerts
|

Integrating organizational learning with high-performance work system and entrepreneurial orientation: a moderated mediation framework

Abstract: This study proposes a moderated mediation model to investigate the relationship between organizational learning and firm performance. We argue that entrepreneurial orientation mediates the positive effect of organizational learning on firm performance. Furthermore, the relationship between organizational learning and entrepreneurial orientation is strengthened when firms employ a higher level of high-performance work system. Hypotheses are supported by data from 181 firms operating in the manufacturing and ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 85 publications
(142 reference statements)
0
17
0
Order By: Relevance
“…A strong OL-CAP enhances firm performance (Goh et al, 2012;Orego and Wainaina, 2019;Wu and Fang, 2010;Zhu et al, 2019) by nurturing and exploiting knowledge to accomplish organizational mission. It enhances innovation and creativity through developing new resources and capabilities to act ahead of changes (Brusoni and Rosenkranz, 2014).…”
Section: Organizational Learning Capability and Firm Performancementioning
confidence: 99%
“…A strong OL-CAP enhances firm performance (Goh et al, 2012;Orego and Wainaina, 2019;Wu and Fang, 2010;Zhu et al, 2019) by nurturing and exploiting knowledge to accomplish organizational mission. It enhances innovation and creativity through developing new resources and capabilities to act ahead of changes (Brusoni and Rosenkranz, 2014).…”
Section: Organizational Learning Capability and Firm Performancementioning
confidence: 99%
“…Additionally, Refs. [3,4] suggested that learning is the "next competitive advantage source" or "only competitive advantage source" [4,5], and, as [6] suggested, "the cornerstone to a company's future success", making it imperative and critical for both scholars. Meanwhile, society has expressed concern about the devastation caused by commercial activities [7], and some businesses have expressed concern about the extent to which all actors are treated ethically and responsibly, as well as the impact of the "stakeholder theory" on organisational performance [6].…”
Section: Introductionmentioning
confidence: 99%
“…Entrepreneurial orientation can be seen as an organization's mentality that represents the attitude of entrepreneurship when starting a new company. Attitude is a central aspect of corporate culture that can be expressed in behaviors such as day-to-day activities and decision-making (Zhu et al, 2018;Zhu, Liu, & Wang, 2019). Furthermore, there is talk of business orientation culture.…”
Section: Resultsmentioning
confidence: 99%